Practical Guide for Forensic Medicine and Toxicology - Tamilmani, K. (Jaypee Brothers Medical Publishers, 2017)
The aim of this book is to focus on practical guide for forensic medicine and toxicology. This book includes discussion of practical aspects of forensic medicine and toxicology in a crystal clear manner, and yet in a nutshell. This book consists of 14 chapters. It includes age estimation by dentition, age estimation by radiograph, examination of skeletal remains, examination of a case of drunkenness, examination of wounds and methods of issuing wound certificate, examination of sexual offence cases, examination of fetus, viscera packing, stature, medicolegal importance of age, various proformas, model spotters and model exercises. This book contains numerous charts, certificates, proformas, tables and photographs, which will be very useful to all. As doctors in every field are exposed to medicolegal aspects, either in our dealings with patients, documentation or certification, a basic knowledge of this field is essential. It is ultimately handy and readily accessible reference guide to forensic medicine and toxicology, students.